Advantages and Disadvantages of Hyperbaric Oxygen Treatment in Mice with Obesity Hyperlipidemia and Steatohepatitis - Koichi Tsuneyama; Yen-Chen Chen; Makoto Fujimoto; Yoshiyuki Sasaki; Wataru Suzuki; Tsutomu Shimada; Seiichi Iizuka; Mitsunobu Nagata; Masaki Aburada; Shao-Yuan Chen (The Scientific World Journal)
The effect of hyperbaric oxygen treatment (HBOT) was examined using MSG mice, which are an animal model of obesity, hyperlipidemia, diabetes, and nonalcoholic fatty liver disease. Nineteen MSG male mice were divided into HBOT treated and control groups at 12 weeks of ages. The HBOT group was treated with hyperbaric oxygen from 12 to 14 weeks (first phase) and then from 16 to 18 weeks (second phase). Interestingly, the body weight of the HBOT group was significantly lower (P<0.01) than that of the control group. In contrast, the serum lipid level did not show significant changes between the two groups. As for the effects of increasing oxidative stress, the liver histology of the HBOT group showed severer cellular damage and aberrant TNF-α expression. HBOT has the advantage of improving obesity in patients with metabolic syndrome, but the fault of causing organ damage by increasing oxidative stress.